PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - SRILESTARI, OCTAVIANA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract : Human resources is one of the key actors in the success of a company. Where the good management of tablespoons can improve the quality of a company. However, the quality obtained often vary it due to the factor of labor discipline and motivation of each individual is different. This study used quantitative research. Where labor discipline and motivation to work as an independent variable and the performance of the employee as the dependent variable. The technique of sampling using the Proportionate stratified random sampling with a sample of 67 full-time employees executing. The analytical method used is multiple linear regression analysis with SPSS software version 18.0. The results showed that 1) working Discipline significant positive effect on employee performance 2) work motivation and a significant positive effect on employee performance 3) work discipline and motivation to work simultaneously affect the performance of employees. Keywords:work discipline, work motivation and employee performance.